Comparative Study of Dexmedtomidine & Propofol Infusion for Intro-Operative Hemodynamic & Recovery Characteristics in Laparoscopic Cholecystectomy – A Prospective, Randomized Control Study - Sarosh Ul Hassan, Nighat Abbas, Sabahat Tariq, Ghulam Murtaza, Arif Iftekhar, Hiba Moazzam, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: This study aims to compare the effectiveness of dexmedetomidine and propofol in responding to hemodynamic changes to pneumoperitoneum during laparoscopic cholecystectomy, as well as to evaluate differences in the time it takes to extubate, the patient's hemodynamic status upon extubation, the patient's level of sedation following extubation, and the occurrence of any side effects. Study Design: Prospective, Randomized Controlled Trial Study Place and Duration: Liaquat National Hospital and Medical College, Karachi. Conducted over a period of 6months from January 2022 to June 2022 Methods: A total of 100 patients (aged 20-60) in Physical Status Classes 1 and 2 as defined by the American Society of Anesthesiologists were randomly split into two groups (P and D). Patients in Group P were given propofol at a rate of 100 micrograms per kilogramme per minute (g/kg/min) after intubation until the end of pneumoperitoneum, while those in Group D were given dexmedetomidine at a rate of 1 micro Multiple readings of HR and MAP were taken at different points in the operation. Measurements of the Resuscitation Success Rate (RSR) and the Modified Alderate Scale (MAS) were also taken 15 and 30 minutes after operation. Results: Showed that during pneumoperitoneum, Group D significantly decreased HR and MAP compared to Group P, which allowed for superior preservation of hemodynamic stability. In contrast to Group P, patients in Group D remained sleepy for up to 30 minutes after surgery. Conclusion: Dexmedetomidine is more effective at suppressing the hemodynamic stress response to pneumoperitoneum during infusion than propofol is, whereas propofol is more effective at speeding up recovery time. Keywords: Dexmedetomidine, hemodynamics, laparoscopy, propofol, pneumoperitonuim